Islamic Reform in Contest: Ahmad Hassan and His Traditionalist Opponents - Akh. Minhaji (Studia Islamika, 2000)
There is a perception, held not only by scholars in the field but by many Muslims as well, that Islamic law in Indonesia is strongly colored by "non-Islamic" local custom (adat). Historically, this notion has given rise to a number of movements which have sought to ensure that religious beliefs and practices be restored and brought into harmony with the primary sources of Islam, the Qur'an and Sunnah. One of these movements was led by Ahmad Hassan (1882-1958), acknowledged by many as a great scholar and a tireless advocate of the need for renewal (tajdid) and reform (ishlah). The organization that he led was Persatuan Islam, popularly known as Persis, a reformist organization that was considered the spearhead of the movement. Hassan was generally considered the foremost proponent of reform amongst Indonesian Muslims, and Accordingly, the criticism directed at him might be seen as a response to the reformers as a whole. It should come as no surprise, however, that his stance on many issues has occasionally elicited hostile reactions.DOI: 10.15408/sdi.v7i2.710